2008
DOI: 10.1523/jneurosci.2680-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1Receptor Modulates Hippocampal Representation Plasticity to Spatial Novelty

Abstract: The human hippocampus is critical for learning and memory. In rodents, hippocampal pyramidal neurons fire in a location-specific manner, forming relational representations of environmental cues. The importance of glutamatergic systems in learning and in hippocampal neural synaptic plasticity has been shown. However, the role of dopaminergic systems in the response of hippocampal neural plasticity to novel and familiar spatial stimuli remains unclear. To clarify this important issue, we recorded hippocampal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 60 publications
4
36
0
Order By: Relevance
“…The targeting vector was constructed so that the entire coding sequence was deleted by using the following DNA fragments: a 1.2 kb MC1 promoter-diphtheria toxin-A fragment gene (DT-A) for negative selection; the XbaI–XbaI fragment containing the upstream region of the D5R gene; a 2.3 kb PGK promoter- Escherichia coli xanthine-guanine phosphoribosyltransferase gene (gpt); a 1.1 kb MC1 promoter-neomycin gene (neo); a 4.0 kb XbaI–NheI fragment containing the 3′-untranslated region; and a pBluescript plasmid (Figure 1a). This targeting vector was then used to generate D1 dopamine receptor-deficient mice [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeting vector was constructed so that the entire coding sequence was deleted by using the following DNA fragments: a 1.2 kb MC1 promoter-diphtheria toxin-A fragment gene (DT-A) for negative selection; the XbaI–XbaI fragment containing the upstream region of the D5R gene; a 2.3 kb PGK promoter- Escherichia coli xanthine-guanine phosphoribosyltransferase gene (gpt); a 1.1 kb MC1 promoter-neomycin gene (neo); a 4.0 kb XbaI–NheI fragment containing the 3′-untranslated region; and a pBluescript plasmid (Figure 1a). This targeting vector was then used to generate D1 dopamine receptor-deficient mice [33].…”
Section: Methodsmentioning
confidence: 99%
“…The ES cell line used for generation of the D5R-KO mice was previously described [33]. Briefly, CCE ES cells (E14TG2a IV 129-derived ES cells, acquired from Dr. E. Robertson) were cultured as described [34].…”
Section: Methodsmentioning
confidence: 99%
“…The deficits observed by D1R KO in these water-based escape tasks is also observed in dry Barnes maze, in which the animal learns to escape from open field into a tunnel, suggesting that the stress of being in the water is not a key factor (Ortiz et al, 2010). In support of D1 receptor mediation of spatial learning, recording from hippocampal place cells in the CA1 region showed that these cells had difficulty adjusting to changes in distal cues in D1R KO mice, an effect that was exacerbated in a novel environment (Tran et al, 2008). Thus, normal signaling through D1 receptors in the hippocampus appears to be modulate the encoding of spatial information.…”
Section: The Role Of Da In Learning and Memorymentioning
confidence: 99%
“…DA influences these properties, as DA agonists increase place field specificity, and DA antagonists and VTA inactivation decrease place field specificity (Kentros et al 2004;Martig and Mizumori 2010). Further, DA regulates place field stability in context-dependent ways (Gill and Mizumori 2006;Tran et al 2008).…”
mentioning
confidence: 99%